2007
DOI: 10.1007/s10750-007-0791-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term colonisation by macroinvertebrates of cobbles in main channel and inundated stream bank habitats

Abstract: In small, forested catchments, short rainfall events cause relatively rapid increases in river discharge that inundate previously dry streamside habitats and last for several days. We examined the colonisation and use of such newly inundated habitats by macroinvertebrates in the riffles of a cobble-dominated river over a 4-day period. First we simulated inundation by adding dry river rocks to the main channel of the stream. Second, we observed colonisation of streamside rocks that were inundated following rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Some studies have reported that different species of invertebrates use refugia differently (e.g., Lancaster & Hildrew, ; Winterbottom et al ., b; Lancaster, ; Holomuzki & Biggs, ; Negishi & Richardson, ; Hose et al ., ). One key factor in the availability of refugia is the mobility of a particular species (Gjerløv, Hildrew & Jones, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that different species of invertebrates use refugia differently (e.g., Lancaster & Hildrew, ; Winterbottom et al ., b; Lancaster, ; Holomuzki & Biggs, ; Negishi & Richardson, ; Hose et al ., ). One key factor in the availability of refugia is the mobility of a particular species (Gjerløv, Hildrew & Jones, ).…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho & Uieda (2004), studying the colonization of ar tificial rock substrates in a forest stream in the Itatinga Mountains in the state of São Paulo, Brazil, repor ted that Chironomidae lar vae were the most abundant group. Hose et al (2007) obser ved a greater density of Chironomidae in rif fle areas along a stony, cobble-dominated stretch of an Australian river in a colonization experiment. Heino & Korsu (2008), studying the relationship between stone surface area and the associated benthic fauna in a temperate climate stream, observed that the Chironomidae were among the most abundant taxa.…”
Section: Introductionmentioning
confidence: 83%
“…These Chironomidae are abundant in the drift of streams during periods of faster water flow and are considered to be rapid colonizers (Hose et al 2007), making them well adapted to live in habitats where the water fl ow is faster (Trivinho-Strixino & Strixino 2005). Hose et al (2007) reported that nearly 70 % of the Chironomidae that colonized the surface of stones that had been disturbed by increased fl ow within a period of 24 hours were composed of Orthocladiinae. Sanseverino & Nessimian (2001) found Or thocladiinae preferentially inhabiting stones exposed to the current in Atlantic Forest streams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the effects of freshwater releases on the macrobenthos community have raised extensive concerns (Dukowska et al, 2007;Hose et al, 2007;Rolston and Dittmann, 2009). Freshwater is an essential resource for maintaining coastal wetlands, as it both alters the salinity and carries an important load of sediment, which contains important nutrients such as organic matter (Naiman and Dudgeon, 2011;Rolls et al, 2012;Shafroth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%